A Review of Commercial Developments and Recent Laboratory Research of Dialyzers and Membranes for Hemodialysis Application - Noresah Said; Woei Jye Lau; Yeek-Chia Ho; Soo Kun Lim; Muhammad Nidzhom Zainol Abidin; Ahmad Fauzi Ismail (Membranes, 2021)
Dialyzers have been commercially used for hemodialysis application since the 1950s, but progress in improving their efficiencies has never stopped over the decades. This article aims to provide an up-to-date review on the commercial developments and recent laboratory research of dialyzers for hemodialysis application and to discuss the technical aspects of dialyzer development, including hollow fiber membrane materials, dialyzer design, sterilization processes and flow simulation. The technical challenges of dialyzers are also highlighted in this review, which discusses the research areas that need to be prioritized to further improve the properties of dialyzers, such as flux, biocompatibility, flow distribution and urea clearance rate. We hope this review article can provide insights to researchers in developing/designing an ideal dialyzer that can bring the best hemodialysis treatment outcomes to kidney disease patients.